Synthesis and Characterisation of Carbon Nanotubes Prepared Using Pulsed Laser Ablation Deposition Technique - Ismail, Ismayadi (2007)
Carbon nanotubes (CNTs) has been the focus of a virtual storm research, both to better understand its unique properties and to harness its potential in commercial applications such as hydrogen storage, atomic force microscopy probe, microelectronic transistor, electrical field emitter of flat panel display. There are two main premises in this research project; the first premise was to synthesis the CNTs via Pulsed Laser Ablation Deposition (PLAD) technique, and the second premise was to study the effect of Fe2O3 as catalyst on the magnetic properties of the deposited materials. This work reports the formation of carbon web-like nano structure synthesized in a T-shape stainless steel chamber. ND:YAG laser with 532nm wavelength and 10.24 W power was used to ablate the target of graphite and catalyst. Fe2O3 and NiO were mixed separately as the catalyst with graphite (carbon) to form the target. The vacuum level was kept at 5 mtorr with argon gas flowing from bottom of the chamber. The soot that was deposited on the glass substrate was then characterized using X-Ray Diffraction (XRD), Scanning Electron Microscope (SEM), Transmission Electron Microscope (TEM), EDX and Vibrating Sample Magnetometer (VSM). The SEM images confirm a web-like structure formed after the ablation. The graphite target that was ablated with laser does not form web-like structure. However, when NiO or Fe2O3 were introduced as the oxide catalysts, the web-like structure was formed successfully. The TEM pictures proved the web-like structure is the carbon nanotubes. Magnetic characterization via VSM was conducted after the CNTs structure was confirmed. From the magnetic characterization, we found that CNTs behaves as non-magnetic material due to the absence of the hysteresis curve. When it was filled with Fe2O3, the magnetic properties enhanced tremendously. It was also concluded that these Fe2O3 nano particles magnetic materials were trapped in the tubes. The CNTs acted as nano-wires and were able to induce the magnetization of the magnetic particles.